Servant Leadership dan Komitmen Organisasi Terhadap Kinerja Karyawan: Studi pada Karyawan CV. Cisarua Cianjur - Intan Permatasari; Nor Norisanti; Faizal Mulia Z (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The company always expects employees to always perform in carrying out their duties and responsibilities to solve problems and prove the hypothesis by collecting data through interviews and questionnaires. The questionnaire was given to 42 respondents, to be further analyzed using multiple linear regression, multiple correlation, F Test and T - Test. Based on the results of calculations using the IBM SPSS Statistics Version 24 program, the results obtained servant leadership has a positive and significant effect on employee performance at CV. Cisarua Cianjur. This means that the better the implementation of servant leadership, the higher the employee performance at CV. Cisarua Cianjur. Organizational commitment has a positive and significant effect on employee performance at CV. Cisarua Cianjur. This means that the more organizational commitment from employees increases, the higher the employee performance at CV. Cisarua Cianjur. Servant leadership and organizational commitment have a positive and significant effect on employee performance at CV. Cisarua Cianjur. This means that the better the implementation of servant leadership and the more organizational commitment from employees increases, the more employee performance at CV. Cisarua Cianjur.